Valorização do trabalho docente ou uma miríade de novas responsabilidades e exigências ao professor nos decretos do governo paulista? - Basílio, Mariana da Rocha [UNESP] (2015)
The concept of social value of teaching today stands out as a current discourse on neoliberalism. In the government of the State of São Paulo, from the beginning of the century, there was a permanent growth of decrees aimed at managing the teaching profession, named in the letter of the law as recovery measures. In the present study we analyze what is the phenomenon of this concept of recovery, seizing new myriad responsibilities and demands on teachers' work in the current government of men, who conceptualizes a reorganization of Taylorism way of work management. For this, we analyze, first, in Chapter 1, from the sociology of work, which is work and teaching work, and its development in the capitalist mode of production, as well as neo-liberalism - also performing, in Chapter 2, one Search in federal constitutions and educational reforms on the concept teacher appreciation. From these discussions, in Chapter 3, we analyzed 14 SP of state decrees on teacher appreciation, found between the years 2010 and 2014 - where we concluded that the State uses the valuation of discourse on the teaching profession to hold a range new responsibilities and demands on the category. We conclude with the studies of these three chapters, that's state laws, from the ordinances of international organizations, an essence that is revealed as a teacher's control, that instead of valuing actually precariza the teaching work, the responsibility for quality education in schools, dividing into different categories and types of employment contract, easing their training and offering small salary adjustments from external evaluation mechanisms, which are presented as a meritocracy policy among teachers. These factors therefore do not value teachers' work, but deprive the teacher of new and real chances of improving the lives and professional environment